Pengembangan Infografis Motion Graphic Tema Lingkungan Sahabat Kita Untuk Kelas V SD - Ari Padrian; Syafril Syafril; Nofri Hendri (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
One of the main problems in teaching and learning process was teacher’s difficulty at providing a fun instructional media so that used is less varied. Infographics motion graphic can help students in understanding subject matter and create a good atmosphere at the learning process. The objectives of this study were (1) Producing good quality infographics of motion graphic media in accordance with feasibility of media evaluation (2) Knowing the feasibility infographics of motion graphic media by theme Lingkungan Sahabat Kita at the 5th grade according to the expert and trial. The research design referring to Borg and Gall Model.The results of analysis based on trials for the practicality infographic motion graphic are in the practical category used evenly overall score of 86,19%.So based on the results of validity and practicality tests it can be concluded that this infographic motion graphic is valid and practical and suitable for use in learning.